A Systematic Review of Fall Risk Factors in Stroke Survivors: Towards Improved Assessment Platforms and Protocols - Abdollahi, Masoud; Whitton, Natalie; Zand, Ramin; Dombovy, Mary; Parnianpour, Mohamad; Khalaf, Kinda; Rashedi, Ehsan (Frontiers in Bioengineering and Biotechnology, 2022)
Background/Purpose: To prevent falling, a common incident with debilitating health consequences among stroke survivors, it is important to identify significant fall-risk factors (FRFs) towards developing and implementing predictive and preventive strategies and guidelines. This review provides a systematic approach for identifying the relevant FRFs and shedding light on future directions of research. Methods: A systematic search was conducted in 5 popular research databases. Studies investigating the FRFs in the stroke community were evaluated to identify the commonality and trend of FRFs in the relevant literature. Results: twenty-seven relevant articles were reviewed and analyzed spanning the years 1995-2020. The results confirmed that the most common FRFs were age (21/27, i.e., considered in 21 out of 27 studies), gender (21/27), motion-related measures (19/27), motor function/impairment (17/27), balance-related measures (16/27), and cognitive impairment (11/27). Among these factors, motion-related measures had the highest rate of significance (i.e., 84% or 16/19). Due to the high commonality of balance/motion-related measures, we further analyzed these factors. We identified a trend reflecting that subjective tools are increasingly being replaced by simple objective measures (e.g., 6-meter walk), and most recently by quantitative measures based on detailed motion analysis. Conclusion: There remains a gap for a standardized systematic approach for selecting relevant FRFs in stroke fall risk literature. This study provides an evidence-based methodology to identify the relevant risk factors, as well as their commonalities and trends. Three significant areas for future research on post stroke fall-risk assessment have been identified: (1) further exploration the efficacy of quantitative detailed motion analysis; (2) implementation of inertial measurement units as a cost-effective and accessible tool in clinics and beyond; and (3) investigation of the capability of cognitive-motor dual-task paradigms and their association with FRFs.